Exploring phenotypic variability in gamma‑irradiated melon (Cucumis melo) for early-generation putative mutant selection - ASTRID IKA PARAMITHA; ARIFIN NOOR SUGIHARTO; BUDI WALUYO; AFIFUDDIN LATIF ADIREDJO; AZERI GAUTAMA ARIFIN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Paramitha AI, Sugiharto AN, Waluyo B, Adiredjo AL, Arifin AG. 2026. Exploring phenotypic variability in gamma‑irradiated melon (Cucumis melo) for early-generation putative mutant selection. Biodiversitas 27 (3): d270324. https://doi.org/10.13057/biodiv/d270324. The melon (Cucumis melo), an agriculturally pivotal crop globally esteemed for its economic value, faces intrinsic breeding limitations due to restricted genetic diversity. Confronting these inherent challenges, gamma irradiation has emerged as a robust mutagenic agent, purposefully employed to elicit phenotypic variability and strategically advance the enhancement of elite melon cultivars. This investigation systematically explored phenotypic modifications induced by six discrete gamma irradiation doses (0-150 Gy) in two melon varieties, CMA and DKN. Comprehensive assessments of fruit weight, flesh thickness, sugar content, and rind color were conducted in the M2 generation, analyzed via descriptive and non-parametric statistics. Results revealed distinct dose-specific responses. Notably, G5 treatment yielded the highest mean sugar content in CMA (10.75°Brix), with DKN exhibiting substantial variation up to 15.00°Brix at G5. Fruit weight demonstrated considerable variability, exemplified by DKN at G1 (0.28-1.92 kg range). Both DKN and CMA consistently achieved their highest mean flesh thickness at G5. Statistical analyses confirmed significant differences across most irradiation doses for sugar content and flesh thickness in both varieties, while fruit weight showed significant effects exclusively at G4 for both CMA and DKN. Crucially, the study identified four novel putative mutant plants: one from CMA (G1) and three from DKN (G5). These putative mutants represent invaluable genetic resources, integrating dark rind color (absent in controls) with quantitative traits was not more than 5% lower than the control mean, thus proving highly advantageous for early generation selection. These findings unequivocally underscore gamma irradiation's profound potential in inducing beneficial phenotypic variability, offering critical foundations for breeding programs targeting enhanced melon fruit quality and marketability.